2017
DOI: 10.1186/s12955-017-0652-6
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver’s quality of life and its positive impact on symptomatology and quality of life of patients with schizophrenia

Abstract: BackgroundAlthough the quality of life (QoL) experienced by patients with schizophrenia has been recognized, few studies have assessed the relationship between the caregivers’ QoL and patients’ QoL.MethodsThe study included 253 stabilized outpatients with schizophrenia and their caregivers from 3 Mental Health Services in Bolivia (N = 83), Chile (N = 85) and Peru (N = 85). Caregivers’ and patients’ QoL were respectively assessed using two specific QoL questionnaires (S-CGQoL and S-QoL 18). We collected socio-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 58 publications
4
23
0
1
Order By: Relevance
“…Health-related QoL is defined as an individual's perception of their position in life, in the context of their culture and value systems, regarding their goals, expectations, standards, and concerns [31]. Caregivers face considerable burdens and challenges relating to their QoL when they support individuals with schizophrenia [32,33], so improvement in the caregiver's QoL has an impact on patient's psychotic symptoms and QoL [34]; thus, focusing on the QoL of family caregivers is crucial for evaluating the critical outcomes of community care.…”
Section: Plos Onementioning
confidence: 99%
“…Health-related QoL is defined as an individual's perception of their position in life, in the context of their culture and value systems, regarding their goals, expectations, standards, and concerns [31]. Caregivers face considerable burdens and challenges relating to their QoL when they support individuals with schizophrenia [32,33], so improvement in the caregiver's QoL has an impact on patient's psychotic symptoms and QoL [34]; thus, focusing on the QoL of family caregivers is crucial for evaluating the critical outcomes of community care.…”
Section: Plos Onementioning
confidence: 99%
“…Finally, Caqueo-Urízar et al presented a bidirectional association between the presence of a caregiver in the quality of life of schizophrenic patients, showing that good quality of life in the caregiver affects the patient positively and vice versa. The study also indicated that the involvement of the family in the patients' lives has a positive impact on their quality of life [8].…”
Section: Discussionmentioning
confidence: 86%
“…The hypothesis was that belonging to an ethnic group (i.e. Aymara vs Non-Aymara) was associated with QoL of schizophrenic patients, based on the results of previous analyses (Caqueo-Urízar et al, 2017a). In this last research, the aim of the study was thus to determine whether caregivers' QoL is a determinant of patients' QoL, while considering other important determinants such as sociodemographic and clinical characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, a recent systematic review described that mental health interventions were associated with improved economic outcomes in lowincome and middle-income countries (Lund et al, 2011). Moreover, poverty worsens the health of patients with schizophrenia, and increases the burden of their caregivers (Butzlaff & Hooley, 1998;Caqueo-Urízar & Gutiérrez, 2006;Karanci, 1995), thus leading to poor QoL scores (Caqueo-Urízar et al, 2017a). This reinforces the need for comprehensive care and special attention should be paid to both objective and subjective quality of life indicators (Boyer et al, 2014).…”
Section: Discussionmentioning
confidence: 99%